EFFECTIVENESS OF TEST DESIGN BETWEEN OF CLOZE TEST AND MULTIPLE CHOICE TEST FOR READING COMPREHENSION - Elma Tiara; Chairuddin Chairuddin; Makhroji Makhroji; Evi Zulida; Fadlia Fadlia; Rahmiati Rahmiati (Journal of Education, Linguistics, Literature and Language Teaching, 2019)
The use of tests that is suitable for use by teachers in learning needs to be considered. This aims to produce a satisfactory of the test result. So the teacher needs to consider what type of test is given to students. So the researcher conducted a study to analyze of effectiveness of test design between of cloze test and multiple choice test for reading comprehension at SMA Negeri 3 Langsa. The purposes of research were to find out if there is a difference between multiple choice test and cloze test in teaching EFL for reading comprehension and to find out which of the most effectiveness between multiple choice tests or cloze test in teaching EFL for reading comprehension. The method of this research is qualitative approach. The sample of this research is the students at class XII Bahasa in SMA Negeri 3 Langsa. In this study, the researcher collected data to conduct on 22nd October 2018 until 19th October 2018 in SMAN 3 Langsa. The result of study showed that the result of testing the students’ reading comprehension showed that the students’ test 1 showed that multiple choice test has mean score 8,1 and cloze test has mean score 7,3. It meant multiple choice test more effective in testing reading comprehension for the students. The result of the students’ test 2 showed that multiple choice test has mean score 8 and cloze test has mean score 5,3. It meant multiple choice test more effective in testing reading comprehension for the students and the result of the teachers’ interview showed that multiple choice test more effective than cloze test but the result of the students’ interview showed that multiple choice test was very difficult. It meant the result of the students’ test between the students’ interview opposite because the students said multiple choice test was very difficult, automatically the students got the multiple choice test score lower than the cloze test score.